Acute toxicity test of Rhizophora apiculata bark extract on rat liver and kidney histology using fixed dose method - Syazili Mustofa; Ilma Puteri Hutami; Dwi Sarwindah (Acta Biochimica Indonesiana, 2023)
Background: The therapeutic properties of the ethanol extract derived from the stem bark of Rhizophora apiculata have been investigated. Nevertheless, there is a lack of studies regarding its acute toxicity. Objective: This research aims to evaluate the toxicity of ethanolic extract of R. apiculata bark by examining histological changes in the liver and kidney of rats. Method: The ethanol extract of R. apiculata bark was administered using a fixed-dose approach in preliminary and primary tests, focusing on the kidneys and liver of male Sprague Dawley rats. Four treatment groups received doses of 5, 50, 300, and 2000 mg/kg BW, while one group served as the control. An uninterrupted observation period of 14 days was conducted to determine any indications of acute toxicity in these animals. On the fifteenth day, the rats were terminated. Results: This study indicated the absence of any toxic manifestations, such as tremors, excessive salivation, convulsions, coma, and mortality. Nevertheless, it caused histological damage to the rats’ liver and kidney when administered at doses 300 and 2000 mg/kg BW. Conclusion: While the administration of R. apiculata extracts at doses of 300 and 2000 mg/kgBW resulted in histological damage to the kidneys and livers of the rats, it did not induce any immediate symptoms.